Financial stability index for the financial sector of Pakistan - Sadia Babar; Rashid Latief; Sumaira Ashraf; Sania Nawaz (Economies, 2019)
This study aims to develop a financial stability index for the Pakistani financial sector by using the financial reports for the period of 2001–2011. Specifically, we constructed three different classes of indices in this study based on a variance-equal weighted approach, a linear probability approach, and a logistic approach. We also assessed the prediction accuracy of the financial stability index. All indices indicated that profitability, liquid liability to the liquid asset, non-performing loan, uncovered liabilities, interest spread and inter-fund to liquid liabilities variables contribute significantly to the determination of financial stress of commercial banks. We also compared the results of indices computed with different methodologies—among them was the index constructed by employing coefficients of the logistic model and which performed outstandingly in predicting distressed and non-distressed banks. Moreover, the findings of this study suggest that in regard to return on assets and return on equity, when employed in a stepwise manner for developing the financial stability index, the results are similar in the sense that both profitability indicators have the same behavior. Finally, we conclude that the financial stability indices developed in this study could help decision makers to detect and avoid instability in the future.
Keywords: P34; G21; G01; 330; financial crises; financial sector; financial stability; financial stability index; financial stress